The Effect Of Teacher Recruitment, Commitment And Compensation On Teacher Performance In SD Negeri 390 And SD Negeri 395 Kecematan Muara Batang Gadis Mandailing Natal Regency - Bolo Ansah Nasution; Yohny Anwar; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
Human Resources (HR) is the most important asset in the implementation of education in schools. In the era of globalization, schools are required to have quality human resources so that they are able to improve the quality of education. As stated in Law of the Republic of Indonesia No. 20 of 2003 concerning the National Education System Article 3 which reads,